Modus Operandi Transaksi Narkotika oleh Anak Melalui Media Digital dan Implikasi Hukumnya - M. Julianto Al Hakim; Diah Gustiniati Maulani; Dona Raisa Monica (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The illicit circulation of narcotics in Indonesia has undergone a fundamental evolution into cyber-enabled crime, where drug syndicates systematically exploit children as technical operators through digital media to sever the main network chain and evade legal detection. This study aims to analyze the anatomy of the modus operandi of narcotics transactions involving children in the digital realm and examine its legal implications for the process of proof and criminal liability. Utilizing an empirical juridical research method with a sociological approach conducted in the jurisdiction of the Metro Police Resort, Lampung, this research identifies a shift in modus operandi towards the